Pricing Strategy Analysis Based on Dual Channel Supply Chain (DCSC) Model Concept - Putri, Nadya Permata; Pulansari, Farida (AFEBI Management and Business Review, 2025)
The rise of digitalization has driven companies to adopt the Dual Channel Supply Chain (DCSC) model to expand market reach and improve distribution efficiency. This study aims to evaluate pricing strategies based on the level of coordination between online, offline, and reseller channels to maximize company profit. The research applies mathematical modeling and numerical simulations across four pricing scenarios, each representing a different level of coordination among distribution channels. Model parameters were obtained from historical company data and customer preference surveys, and analyzed using MATLAB software. Simulation results show that Scenario 2, integrating coordination among online, external reseller, and offline channels, yields the highest financial performance, generating a total profit of IDR 456,955,350. This collaborative approach outperforms other scenarios by enabling synchronized pricing and promotions and expanding market coverage without requiring additional investment in distribution infrastructure. Further sensitivity analysis confirms that Scenario 2 remains the most robust across variations in key parameters such as unit cost, channel preference, and maximum demand. Therefore, a coordinated pricing strategy within the DCSC framework can serve as an adaptive and competitive solution for companies operating in multi-channel environments.